The Role of Islamic Religious Education Teachers in the "Program Sekolah Penggerak" at Public Elementary Schools - Maskanah, Ulfa; Marno, Marno (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
Education in Indonesia aims to develop abilities and shape the character and civilization of a dignified nation. However, there are various challenges to its implementation. For this reason, the government launched "Program Sekolah Penggerak (PSP)" to improve the quality of education. This study aims to determine the implementation of the "PSP" at Public Elementary Schools. The method used was qualitative with the type of field research. Data were collected through observation, interviews, and documentation studies at Public Elementary School (SDN) 2 Banyu Urip. The results showed: 1. The SDN 2 Banyu Urip had implemented five interventions of "PSP" including asymmetric mentoring, strengthening human resources, learning with a new paradigm, data-based planning, and school digitalization. 2. The "PSP" affects five PAI teacher competencies. 3. PAI teachers play a role in programs such as the Pancasila Student Profile Strengthening Project (P5). 4. The challenges faced by PAI teachers include difficulties in collaborating with parents and the community. This study provides an overview of how the role of PAI teachers can be optimized to support the success of the "PSP."